Bingo! Holy play in experience-oriented society. (June 2017) - De Groot, Kees
What place is there for holy play in experience-oriented society? Is it possible and useful to make analytic distinctions between the liturgical quality of events? I explored these questions by doing research on the boundaries between the religious field and the field of leisure. Fifty site visits to public events in the Netherlands (2006–2014) resulted in a collection of ethnographic data. I used the concept of play as introduced by the Dutch historian Johan Huizinga and the tools of ritual studies to explore whether these could help to produce an account of the liturgical quality of ritualized meetings. Holy play might be found in unexpected places, such as in a bingo hall. Huizinga's broad diagnosis of modernity may be outdated, but the tools he introduced remain useful to distinguish the elements that constitute late-modern meetings as more or less playful – even when this involves combinations that seem contradictory from Huizinga's own point of view.